Enzymosomes- A Pioneering Advancement in Targeted Vesicular Drug Delivery - Preeti Meshram; Dr.Nisha Ranpise; Ramesh Gadekar; hagyashreewarude; Shyam Awate; Sharvari Chavan; Dr.Trupti Tuse; Dipali Kulkarni; Hemlata Wadkar; Pallavi Nigade (International Journal of Pharma and Bio Sciences, 2022)
Vesicles are colloidal particles which have a concentric bilayer made up of amphiphilic molecules surrounding an aqueous compartment. An innovative and currently emerging targeted vesicular drug delivery system (VDDS) that sustains the drug release at a predetermined rate and overcomes the limitation of conventional drug delivery systems. The enzymes which have targeted catalytic function for a substrate are incorporated within cell-like structures having high lipophilicity. These cell-like structures coupled covalently to the surface of enzyme improves absorption through a biological membrane and prevent degradation. Enzymes used includes Carboxypeptidase G2. β-Vesicles are colloidal particles that have a concentric bilayer made up of amphiphilic molecules surrounding an aqueous compartment. An innovative and currently emerging targeted vesicular drug delivery system (VDDS) which sustains the drug release at a predetermined rate and overcomes the limitation of conventional drug delivery systems. The enzymes which have targeted catalytic function for a substrate are incorporated within cell-like structures having high lipophilicity. These cell-like structures coupled covalently to the surface of the enzyme improve absorption through a biological membrane and prevent degradation. Enzymes used include Carboxypeptidase G2, β-acylation which were made direct conjugation, physical adsorption, encapsulation methods to organize enzymosomes with targeted action. It also minimizes alterations within the normal enzymatic activity, thus enhancing half-life and achieving enzyme activity on targeted sites like cancerous cells. They are a promising substitute to standard treatment therapies of gout, anti-platelet activities, etc. This review discusses the various application of therapeutic enzymes coupled in VDDS, the composition of enzymology, its structure, advantages, disadvantages, various pharmacological targeted delivery, and medical applications of Lactamase, and lipids like Sphingolipids. Enzymes were linked through acylation, direct conjugation, physical adsorption, encapsulation methods to organize enzymosomes with targeted action. It also minimizes alterations within the normal enzymatic activity, thus enhancing half-life and achieving enzyme activity on targeted sites like cancerous cells. They are a promising substitute to standard treatment therapies of gout, anti-platelet activities, etc. This review also explains the incorporation of application of various therapeutic enzymes like SOD, Uricase, Candida utilis showing antiplatelet activity, anticancer, antiarthritic activities which summarises all case studies in a single article.